The diffusion of innovations in the world textile industry: does a country's level of economic development matter? - Matthias Lücke (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
This paper provides empirical evidence on how the international diffusion of industrial process innovations is affected by a country's level of economic development. It analyses annual data on newly installed machinery in the spinning and weaving industries, where open-end rotors and shuttleless looms, respectively, represent easily identifiable innovations. A variable coefficient model, based on an S-shaped diffusion curve, is estimated from pooled data to assess the impact of the level of economic development on the diffusion of each innovation. It is found that the level of economic development affected the timing of the start of the diffusion process, but not the speed of diffusion within each country.
Keywords: O14; O33; 330